Archimedes Screw Turbine Application on Portable Mini Hydropower Plant - RD Kusumanto; M. Noviansyah Nugraha; Indrayani Indrayani (Politeknik Negeri Lhokseumawe, 2023)
In this Turbine Design Analysis, we can obtain the necessary measurement results from one of the river locations where research is conducted. The original data for this objectivity was gathered by the authors through direct examination of the area or research site. This data was gained by three measurements: a direct survey of the location, quantitative measurements, and an analysis of the collected data. The authors obtain the necessary data such as differences in water level elevation (Head), Measurement of water discharge distribution (V), width of function on the river (L), and river area (A) and water discharge from the results of measurements to sites (Q). The tool's turbine efficiency has been calculated to be 55.6% based on the results of an analysis. Based on the acquired study, the developed turbine has two threads, a screw tilt angle of twenty-two degrees, and a length of eighty centimeters. In theoretical calculations, the hydropower's (PHydropower) generation power is 1114.42 Watt, the turbines (PTurbines) generation power is 664.2 Watt, and the generator's (PGenerator) generation power is 564.6 Watt. This value is used as a reference for selecting the type of generator to be utilized in the tool's design. Measurement of rotation of turbines the optimal turbine tilt angle for creating optimal turbine rotation is 30 degrees, resulting in a turbine speed of 402 revolutions per minute. The turbine tilt angle of 30 degrees (Optimal Angle) delivers the best results with an Electric Voltage (V) of 12.77 Volts and an Electric Current (I) of 2.51 Amps, according to the design tool's measurement data. Based on the results of an examination of electrical power output, a turbine tilt angle of 30° (Optimal Angle) delivers the best results with a residual power of 80 to 150 Watts when using a design tool suitable to steady and fast discharge conditions